PERLINDUNGAN HUKUM TERHADAP KORBAN KEKERASAN PSIKIS DALAM LINGKUP RUMAH TANGGA - Rani Iriyani (Journal of Law ( Jurnal Ilmu Hukum ), 2020)
ABSTRACT Psychic violence is violence that cannot be seen in plain view or can be said to be hidden violence. Psychic violence can be in the form of verbal assumptions, attitudes, or actions that are not pleasant. Psychic violence is far more painful because it can damage a person's honor, hurt one's self-esteem, and also damage the balance of the soul.The problem in this thesis is how to regulate the legal protection of victims of psychological violence in the scope of the household, how the form of legal protection against victims of psychological abuse in the scope of the household.In discussing these problems, it can be concluded that the regulation of legal protection for victims of psychological violence in the sphere of the household is Law Number 23 of 2004 concerning the Elimination of Domestic Violence and Government Regulation Number 4 of 2006 concerning the Implementation and cooperation of Recovery of Victims of Domestic Violence  The form of protection for victims of psychological violence in the household sphere is prevention, treatment and recovery. Keywords: Legal Protection, Psychic Violence